Comparative Evaluation of Morpho-Functional Characteristics of Cryopreserved Multipotent Mesenchymal Stromal Cells From Different Sources - Vvedenskyi, Dmytro B.; Volkova, Nataliia O.; Goltsev, Anatolyi M. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 175.